2015
DOI: 10.1111/bju.13155
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous nephrolithotomy in super obese patients (body mass index ≥ 50 kg/m2): overcoming the challenges

Abstract: ObjectiveTo analyse our experience with and the outcomes and lessons learned from percutaneous nephrolithotomy (PCNL) in the super obese (body mass index [BMI] ≥50 kg/m 2 ). Patients and MethodsIn this institutional review board approved study we retrospectively reviewed our PCNL database between July 2011 and September 2014 and identified all patients with a BMI ≥ 50 kg/m 2 . Patient demographics, peri-operative outcomes and complications were determined. Additionally, we identified a number of special PCNL c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 39 publications
0
15
1
Order By: Relevance
“…They emphasize the importance of the entire care team, incorporating an anesthesiologist comfortable with prone positioning and airway concerns in obese patients. 17 While the two previously described studies have demonstrated the feasibility of PCNL in even the largest patients, ours is the first to indicate acceptable outcomes with PCNL in a direct comparison between superobese patients and those with lower BMI. These findings are important in the context of the increasing use of flexible ureteroscopy, especially for larger renal stones.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…They emphasize the importance of the entire care team, incorporating an anesthesiologist comfortable with prone positioning and airway concerns in obese patients. 17 While the two previously described studies have demonstrated the feasibility of PCNL in even the largest patients, ours is the first to indicate acceptable outcomes with PCNL in a direct comparison between superobese patients and those with lower BMI. These findings are important in the context of the increasing use of flexible ureteroscopy, especially for larger renal stones.…”
Section: Discussionmentioning
confidence: 51%
“…11 Several studies have documented the feasibility, safety, and efficacy of PCNL in obese patients. [12][13][14] However, limitations such as small sample size, 15 lack of comparator groups, 16,17 or few patients at BMI extremes 18 have led some experts to assert that alternative treatment modalities, namely flexible ureteroscopy, be considered first-line therapy. 19 Herein, we present our experience and outcomes following PCNL in patients across a wide range of BMI from a large, single-institutional contemporary dataset.…”
Section: Introductionmentioning
confidence: 99%
“…Further randomized clinical trials of a large sample size in obese patients are required to recommend an extensive application of supine PCNL as an alternative to prone PCNL. The recognized challenges and effects in the application of PCNL in obese patients also include poor radiographic or ultrasonographic visualization, difficulties in identifying anatomic landmarks and in reaching the kidney because of excess fat tissue, stone location, and the safe positioning of patients [21] . The calyceal site was associated with decreased fitness for surgery and an increased risk of postoperative complications compared to the renal site [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative considerations and instrument modifications were suggested for overcoming certain challenges; those included using the shortest possible access tract, extra long access sheaths, wide incision of the skin and subcutaneous tissue in addition to postoperative drainage with nephroureteric tubes rather than with nephrostomy tubes. 9 In terms of blood transfusion rates, obesity was not associated with an increase need of blood transfusions. This study showed that transfusion requirements among the 4 groups was not statistically significant (p=0.103).…”
Section: Discussionmentioning
confidence: 91%